Safety, efficacy and acceptability of praziquantel in the treatment of Schistosoma haematobium in pre-school children of Kwale County, Kenya. - Bridget W Kimani; Amos K Mbugua; Jimmy H Kihara; Murima Ng'ang'a; Doris W Njomo (Public Library of Science (PLoS), 2018)
BACKGROUND:The recommended strategy for control of schistosomiasis is preventive chemotherapy with praziquantel (PZQ). Pre-school children (PSC) are excluded from population treatment programs. In high endemic areas, these children are also at risk, and require treatment with PZQ. The Government of Kenya initiated the National School-Based Deworming Programme (NSBDP) where PSC in Early Childhood Development Education (ECDE) Centers are only eligible for treatment with albendazole (ABZ) but not with PZQ. METHODOLOGY/PRINCIPAL FINDINGS:400 PSC were enrolled, from 10 randomly selected ECDE Centers in Kwale County, Kenya where children were treated with crushed PZQ tablets mixed with orange juice, at a single dose of 40 mg/kg. Adverse events were assessed 24 hours post-treatment through questionnaires administered to the parents or guardians. Acceptability was determined by observing if the child spat and/ or vomited all or part of the PZQ dose immediately after treatment. Efficacy was assessed by examining urine samples for Schistosoma haematobium eggs in the 5 weeks post-treatment follow-up. Children testing negative for S. haematobium during the follow-up were considered cured. Egg reduction rate (ERR) was calculated as the decrement in the infection intensity (group's geometric mean egg counts per 10 ml of urine) following treatment expressed as a proportion of the pre-treatment infection intensity. Before treatment, 80 out of the 400 children enrolled in the study tested positive for S. haematobium (20.0% (95% confidence interval (CI) 16.4-24.2%). Of these, 41 had infections of heavy intensity (51.3%) while the rest (48.7%) were of light intensity. Five weeks post-treatment, 10 children who had heavy intensity infection were diagnosed with S. haematobium (prevalence: 2.5% (95% CI 1.5-4.9%). Infection intensities decreased significantly from 45.9 (95% CI: 31.0-68.0) eggs/ 10 ml urine to1.4 (95% CI: 1.1-1.7) eggs/ 10 ml urine during pre-and post-treatment respectively. The ERR was 96.9%. There were no severe adverse events during follow up 24 hours post treatment. Treatment tolerability among the 400 children was high as none of the children spat and/ or vomited as observed in this study. CONCLUSION/SIGNIFICANCE:The study revealed that crushed PZQ is safe and effective in the treatment of urogenital schistosomiasis in this age group. It is therefore recommended that PZQ should be administered to the PSC in Kwale County.